RESPONS PERTUMBUHAN BIBIT KAKAO (Theobroma cacao. L) TERHADAP PEMBERIAN KOMPOS BLOTONG DAN PUPUK NPKMg PADA MEDIA SUBSOIL ULTISOL - Agustua Sinabariba; Balonggu Siagian; Sanggam Silitonga (Jurnal Agroekoteknologi, 2013)
This research aims to test the response of seedling growth of cocoa (Theobroma cacao L) againstNPKMg fertilizer (15: 15: 6: 4) and the filter cake compost on soil media subsoild Ultisol. Thisresearch using randomized block design (RBD) factorial with 2 (two) treatment factors. The firsttreatment is: Compost filter cake with 4 level: M0 = subsoil Ultisol + compost filter cake (5kg+ 0 kg), M1 = subsoil Ultisol + compost filter cake (3.75 kg + 1.25 kg), M2 = subsoil Ultisol +compost filter cake (2.5 kg + 2.5 kg) , M3 = subsoil Ultisol + compost filter cake (1.25 kg+ 3.75 kg). The second factor, namely: Fertilizer dose NPKMg follows: P0 = 0 g / polybag,P1 = 3 g / polybag, P2 = 6 g / polybag and P3 = 9 g / polybag. Parameters measured wereseedling height, stem diameter, number of leaves, total leaf area, canopy wet weight, dry weightcrown, root wet weight and dry weight of roots. The result showed that the treatment effect is notreal compost filter cake growth of cocoa seedlings. NPKMg fertilizer treatment significantlyinfluenced all parameters were observed, namely: plant height, stem diameter, number of leaves,canopy wet weight, dry weight crown, root wet weight and dry weight of roots. Interactionblotong compost and fertilizer NPKMg unreal effect on the growth of cocoa seedlings..Keywords: cocoa seeds, compost and fertilizer blotong NPKMg